Environmental and resource evaluation of smelter slag - Malovanyy, Myroslav; Ilyash, Oksana; Povzun, Oleksiy; Stepanets, Oleg; Serga, Tatiana; Gubar, Oksana; Serdyuk, Volodymyr (Видавництво Львівської політехніки, 2020)
The gross emission of harmful substances (dust) while unloading the smelter slag of PJSC “Mariupol Iron and Steel Works” into the waste heaps from the dump truck body and during their storage was calculated. The expediency of restoration of blast furnace slag as a siliceous component in cellular concrete was proved. The optimal compositions of cellular concrete mixtures (including the addition of TLS plasticizer – technical lignosulfonate) were determined based on the following criteria: average density of cellular concrete in the dry state and its compressive strength.
Keywords: smelter slag; dust; recovery of blast furnace slag